Association Between CT Attenuation and Mechanical Basket Lithotripsy Failure in Common Bile Duct Stones: A Single-Centre Retrospective Exploratory Study - Takafumi Tanimoto; Kohsaku Ohnishi; Yuki Ito; Yuhiko Katanosaka; Naoko Hayata; Akino Okamoto; Hiroki Murai; Tomohide Kurahashi; Shigeki Suemura; Motohiro Hirao; Takuya Yamada; Atsushi Hosui (Journal of Clinical Medicine, 2026)
Background: Mechanical lithotripsy is used for difficult common bile duct (CBD) stones, but failure to fragment a grasped stone can complicate endoscopic management. Evidence regarding the association between preprocedural computed tomography (CT) attenuation and mechanical lithotripsy outcome is limited. This study explored the association between CT attenuation of CBD stones and mechanical basket lithotripsy failure in a single-centre retrospective cohort. Methods: We retrospectively analysed 37 patients in whom a CBD stone was grasped with a basket catheter, could not be extracted directly, and underwent attempted intraductal mechanical crushing between 1 April 2017 and 31 March 2023. Lithotripsy failure was defined as inability to fragment the grasped stone despite use of a dedicated crusher handle. Continuous variables were compared using the Mann–Whitney U test and categorical variables using Fisher’s exact test. CT attenuation analyses were restricted to CT-positive stones with measurable attenuation values (n = 27). Exploratory receiver operating characteristic (ROC) analyses were performed, and areas under the curve (AUCs) were accompanied by nonparametric bootstrap 95% confidence intervals (CIs) based on 10,000 resamples. No clinical CT attenuation threshold was proposed. Results: Mechanical lithotripsy succeeded in 31 patients and failed in 6. CT attenuation was measurable in 27 patients (21 successes and 6 failures). Among these patients, the failure group had higher mean CT attenuation than the success group (median 241 [IQR 217.8–473.5] HU vs. 76 [67–88] HU; p = 0.00064) and higher maximum CT attenuation (386 [269.8–589.3] HU vs. 123 [102–133] HU; p = 0.00133). Exploratory ROC analysis showed an AUC of 0.968 (bootstrap 95% CI, 0.871–1.000) for mean CT attenuation and 0.940 (bootstrap 95% CI, 0.800–1.000) for maximum CT attenuation. These estimates were derived and evaluated in the same small dataset and were therefore considered exploratory. Conclusions: In this small, selected retrospective cohort, higher CT attenuation values were observed among the six patients with mechanical basket lithotripsy failure. These findings are exploratory and require confirmation in larger prospective studies using standardized CT protocols before CT attenuation can be incorporated into procedural decision-making.